Structural insights into the interactions of phorbol ester and bryostatin complexed with protein kinase C: a comparative molecular dynamics simulation study - Thangsunan P. (2017)
© 2015 Informa UK Limited, trading as Taylor & Francis Group. Protein kinase C (PKC) isozymes are important regulatory enzymes that have been implicated in many diseases, including cancer, Alzheimer’s disease, and in the eradication of HIV/AIDS. Given their potential clinical ramifications, PKC modulators, e.g. phorbol esters and bryostatin, are also of great interest in the drug development. However, structural details on the binding between PKC and its modulators, especially bryostatin – the highly potent and non-tumor promoting activator for PKCs, are still lacking. Here, we report the first comparative molecular dynamics study aimed at gaining structural insight into the mechanisms by which the PKC delta cys2 activator domain is used in its binding to phorbol ester and bryostatin-1. As anticipated in the phorbol ester binding, hydrogen bonds are formed through the backbone atoms of Thr242, Leu251, and Gly253 of PKC. However, the opposition of H-bond formation between Thr242 and Gly253 may cause the phorbol ester complex to become less stable when compared with the bryostatin binding. For the PKC delta-bryostatin complex, hydrogen bonds are formed between the Gly253 backbone carbonyl and the C30 carbomethoxy substituent of the ligand. Additionally, the indole Nε1 of the highly homologous Trp252 also forms an H-bond to the C20 ester group on bryostatin. Backbone fluctuations also suggest that this latter H-bond formation may abrogate the transient interaction between Trp252 and His269, thus dampening the fluctuations observed on the nearby Zn 2+ -coordinating residues. This new dynamic fluctuation dampening model can potentially benefit future design of new PKC modulators.